Contraceptive exposure associates with urinary tract infection risk in a cohort of reproductive-age women: a case control study. (2nd January 2023) - Lo, Claire; Abraham, Abin; Bejan, Cosmin A.; Reasoner, Seth A.; Davidson, Mario; Lipworth, Loren; Aronoff, David M.
Abstract: Purpose: Although non-barrier contraception is commonly prescribed, the risk of urinary tract infections (UTI) with contraceptive exposure is unclear. Materials and methods: Using data from Vanderbilt University Medical Centre's deidentified electronic health record (EHR), women ages 18–52 were randomly sampled and matched based on age and length of EHR. This case-control analysis tested for association between contraception exposure and outcome using UTI-positive (UTI+) as cases and upper respiratory infection+ (URI+) as controls. Results: 24, 563 UTI + cases (mean EHR: 64.2 months; mean age: 31.2 years) and 48, 649 UTI-/URI + controls (mean EHR: 63.2 months; mean age: 31.9 years) were analysed. In the primary analysis, UTI risk was statistically significantly increased for the oral contraceptive pill (OCP; OR = 1.10 [95%CI = 1.02–1.11], p  ≤ 0.05), intrauterine device (IUD; OR = 1.13 [95%CI = 1.04–1.23], p  ≤ 0.05), etonogestrel implant (Nexplanon ® ; OR = 1.56 [95% CI = 1.24–1.96], p  ≤ 0.05), and medroxyprogesterone acetate injectable (Depo-Provera ® ; OR = 2.16 [95%CI = 1.99–2.33], p  ≤ 0.05) use compared to women not prescribed contraception. A secondary analysis that included any non-IUD contraception, which could serve as a proxy for sexual activity, demonstrated a small attenuation for the association between UTI and IUD (OR = 1.09 [95%CI = 0.98–1.21], p  = 0.13). Conclusion: This study notes potential for a small increase in UTIs with contraceptive use. Prospective studies are required before this information is applied in clinical settings. Condensation: Although non-barrier contraception is commonly prescribed, the risk of urinary tract infections (UTI) with contraceptive exposure is poorly understood. This large-cohort, case-control study notes potential for a small increase in UTIs with contraceptive use.